« C’est eux contre nous » ou « Qui a peur de qui ? » : la rhétorique post-11 septembre de l’administration américaine vue par la caricature de presse - Dominique CADINOT (E-REA)
In the months following the September 11 attacks on New York and Washington when the anti-terrorist phobia was at its peak, very few Americans dared voice criticism of the Bush administration’s assault on civil liberties. Even fewer commentators dared to use humor in dealing with the tragedy. However, despite the context, on December 15th, three months after the attacks, Atlanta’s major daily newspaper, TheAtlanta Journal-Constitution, ran an editorial cartoon drawn by Mike Luckovich questioning John Ashcroft’s management of the USA PATRIOT Act.The apparent purpose of the caricature is to satirize the way the Arab or Muslim communities are stigmatized as “enemies within” and to critique the artificial dichotomy used by the administration: “Us versus them”.However, the decision to depict John Ashcroft, leader of the domestic war-on-terror apparatus and prominent evangelist, indicates that what is at stake here is the thorny issue of the relations between state power and religion.Since cartoons may provide scholars with a glimpse of the political debate or public opinion surrounding past events, this essay will seek to highlight and reflect on the feelings of millions of Americans who, a few months after the implementation of the national security strategy, initiated a response to those confounding patriotism and bigotry.